1997
DOI: 10.1038/sj.ijo.0800443
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and nature of dietary underreporting in a free-living population: the Fleurbaix Laventie Ville Santé (FLVS) study

Abstract: OBJECTIVE: To study the determinants and nature of dietary underreporting in a free-living population. DESIGN: Cross-sectional study of nutritional and behavioural characteristics. SUBJECTS: 1030 weight-stable subjects, 501 women and 529 men older than 15 y, included in the Fleurbaix Laventie Ville Sante  study. MEASUREMENTS: Dietary intake was assessed using a 3 d dietary record. Self assessed body weight and height were also recorded. Behavioural and socio-economic data were obtained from a questionnaire. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
132
3
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(148 citation statements)
references
References 33 publications
10
132
3
3
Order By: Relevance
“…This procedure, known as the Goldberg cut-off technique, has demonstrated a widespread tendency to underestimation in large national dietary surveys from several countries as well as in many smaller surveys (Heywood et al, 1993;Fogelholm et al, 1996;Briefel et al, 1997;Lafay et al, 1997;Price et al, 1997;Pryer et al, 1997;Rothenberg et al, 1997;Voss et al, 1998). However, this technique was devised to evaluate the overall bias towards under-reporting at the group level.…”
Section: Introductionmentioning
confidence: 99%
“…This procedure, known as the Goldberg cut-off technique, has demonstrated a widespread tendency to underestimation in large national dietary surveys from several countries as well as in many smaller surveys (Heywood et al, 1993;Fogelholm et al, 1996;Briefel et al, 1997;Lafay et al, 1997;Price et al, 1997;Pryer et al, 1997;Rothenberg et al, 1997;Voss et al, 1998). However, this technique was devised to evaluate the overall bias towards under-reporting at the group level.…”
Section: Introductionmentioning
confidence: 99%
“…In 63 % of groups mean EI was more than 10 % below mean EE and in only one group was it more than 10 % above EE. Comparisons of EI expressed as a multiple of BMR (EI : BMR) with the physical activity level (PAL) for a sedentary lifestyle have confirmed the widespread tendency to underestimation of EI in large national dietary surveys from several countries (Heywood et al 1993;Klesges et al 1995;Ballard-Barbash et al 1996;Fogelholm et al 1996;Briefel et al 1997;Lafay et al 1997;Price et al 1997;Pryer et al 1997;Rothenberg et al 1997;Braam et al 1998;Gnardellis et al 1998;Voss et al 1998) and also many smaller studies. Mean reported EI : BMR values were predominantly in the range of 1⋅2-1⋅5, whereas DLW studies suggest that EE is greater than 1⋅55 × BMR in all age groups except those aged over 75 years .…”
mentioning
confidence: 86%
“…23,24 This under-reporting, primarily by overweight and obese persons, may be specific to energy-dense snack and dessert-type foods. [25][26][27][28] We recently reported that implausible energy intakes affect apparent eating patterns as well, being associated with lower reported meal and snack frequencies, energy densities and portions consumed. 9,10,22 With aging comes a decline in the ability to regulate food intake.…”
Section: Introductionmentioning
confidence: 99%
“…As it has been well established that overweight and obese individuals under-report energy intake by 30-50%, 23,24 and physiologically implausible reporters may contribute to inaccuracy in relationships between dietary factors and BMI, 22,27,[38][39][40][41] we utilized our recently validated method for identifying implausible energy intake reports (i.e., those incompatible with long-term weight stability) 22 and limited our analysis to only those subjects reporting physiologically plausible energy intakes. We hypothesized that older subjects would have weaker associations of dietary factors with BMI compared to younger subjects.…”
Section: Introductionmentioning
confidence: 99%